STUDI TENTANG BENTUK, MOTIF DAN TEKNIK KRIYA PERAK KOTO GADANG MINANGKABAU - Kamal, M. Nasrul (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
Silver is a white shiny metal. It is used as daily needs as well as decoration. The silver handicraft in Koto Gadang district have been well-known since long time ago. The things made by each handycraft centers are almost the same so that it is difficult to create interesting shapes for consumers. Beside that, the technique used is still a simple one, and the motives applied to the handicraft are only little developed. Therefore, this research tries to describe several things: 1) To identify silver handicraft product shapes; 2) To identify the name of the motives being developed; 3) To explain the production technique of silver handicraft. This research is conducted in Koto Gadang; using quantitative and qualitative sampling. The result of this research is silver handicraft shapes, which involve various kinds of earring, bracelet, brooch, ring, necklace, pendant, and miniature, as well as ornament for wedding ceremnny, among other things are various shapes of necklace, ring, and ear-plug. To make handicraft, chisel, kikir (serrated iron for smoothing something), plait, and sickle. The motives applied on the products are cucumber leaf, padek leaf, jackfruit leaf,